A New Way Out of the Predicament of Anaplastic Thyroid Carcinoma From Existing Data Analysis - Zhou, Yikun; Zhao, Yang; Ding, Xi; Liang, Jing; Xu, Huayang; Lin, Yuxuan; Khan, Hamad Haider; Shi, Bingyin (Frontiers in Endocrinology, 2022)
Background: Anaplastic thyroid carcinoma (ATC) is an endocrine tumor with a low incidence but a very poor prognosis. The vast majority of patients have a survival time of only three to six months, but a few survive for two years or more. In recent years, there have been major breakthroughs in targeted and immunotherapy in the field of oncology therapy. Although the preliminary study for ATC showed a promising prospect, more clinical trials are needed. It is the best approach to explore the measures that can improve survival time of ATC from the available clinical data, especially those with long survival. Methods: We report on an 82-year-old ATC patient who survived for 3 years and systematically review the clinical characteristics of 45 ATC patients with complete data from the two largest centers in northwest China. In particular, factors related to long-term survival were analyzed and summarized. Results: Three years prior, an 82-year-old woman was diagnosed with ATC by core needle biopsy following a physical examination. The thyroid tumor was resected within one month, and then the patient was treated with radiotherapy. The patient was still healthy after three years of follow-up. Analysis of prognostic factors for the 45 reviewed patients showed that those undergoing radical surgery (median overall survival (OS) = 472 days, p = 0.0261) and radiotherapy (median OS = 220 days, p = 0.0136) had better outcomes. In addition, patients younger than 65 years (median OS = 164.5 days, p = 0.0176) and with a lower tumor stage (IV A, median OS = 633.5 days, p = 0.0191) also had a better outcome. Conclusion: ATC is a highly malignant tumor, but timely early diagnosis and standardized treatment with radical surgery and radiotherapy as the core can achieve good results. Some patients can achieve long-term survival.